Side channel power analysis on a target with an AES-256 encryption - Yeow, Jun Wei (Nanyang Technological University, 2023)
Side-channel attacks (SCA) are attacks launched by cyber attackers to uncover information from cryptography devices. This information may include confidential plaintexts or secret keys used for encryption, and hence highlights the need for further studies in protecting ourselves against such attacks. In this report, we will discuss how Power Analysis Attacks may be used by attackers to uncover our confidential information. Two main forms of analysis attacks will be discussed – namely correlation and differential power attacks. The focus of the report will be on how these power attacks work and will discuss the results of our experiments on implementing these forms of attacks on devices under Advanced Encryption Standard (AES).